Heterotrophic cultivation of Auxenochlorella protothecoides using forest biomass as a feedstock for sustainable biodiesel production - Patel, Alok (Biotechnol Biofuels, 2018)
BACKGROUND: The aim of this work was to establish a process for the heterotrophic growth of green microalgae using forest biomass hydrolysates. To provide a carbon source for the growth of the green microalgae, two forest biomasses (Norway spruce and silver birch) were pretreated with a hybrid organosolv-steam explosion method, resulting in inhibitor-free pretreated solids with a high cellulose content of 77.9% w/w (birch) and 72% w/w (spruce). Pretreated solids were hydrolyzed using commercial cellulolytic enzymes to produce hydrolysate for the culture of algae. RESULTS: The heterotrophic growth of A. protothecoides was assessed using synthetic medium with glucose as carbon source, where the effect of sugar concentration and the carbon-to-nitrogen ratio were optimized, resulting in accumulation of lipids at 5.42 ± 0.32 g/L (64.52 ± 0.53% lipid content) after 5 days of culture on glucose at 20 g/L. The use of birch and spruce hydrolysates was favorable for the growth and lipid accumulation of the algae, resulting in lipid production of 5.65 ± 0.21 g/L (66 ± 0.33% lipid content) and 5.28 ± 0.17 g/L (63.08 ± 0.71% lipid content) when grown on birch and spruce, respectively, after only 120 h of cultivation. CONCLUSIONS: To the best of our knowledge, this is the first report of using organosolv pretreated wood biomass hydrolysates for the growth and lipid production of microalgae in the literature. The pretreatment process used in this study provided high saccharification of biomass without the presence of inhibitors. Moreover, the lipid profile of this microalga showed similar contents to vegetable oils which improve the biodiesel properties.